Amorphous nanocrystalline ribbon magnetic core and its preparation method and application
By rolling and rolling annealing of amorphous nanocrystalline strips and applying tension stress, the preparation process of nanocrystalline magnetic cores is simplified, and the problems of narrow application range and complex process in the existing technology are solved, and the continuous adjustability and performance improvement of magnetic permeability are achieved.
Patent Information
- Application Number
- CN202311000943.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-08-10
AI Technical Summary
The prior art has problems with narrow applicable system scope, complex processing process steps and narrow permeability coverage when preparing nanocrystalline magnetic cores, which are difficult to meet the performance requirements of high-frequency inductors.
The amorphous nanocrystalline strip roll annealing step is made by applying tensile stress along the length direction of the strip to form a closed magnetic circuit or stacked layer to form a block, simplifying the preparation process and achieving continuous adjustable magnetic permeability.
The magnetic permeability coverage range of 50-30,000 is achieved, which reduces production costs, simplifies the process, and improves the performance of the product.
Smart Images

Figure CN117095933B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of soft magnetic materials and inductor components, and specifically relates to an amorphous nanocrystalline ribbon magnetic core and a preparation method and application thereof. Background Art
[0002] With the popularization of the third generation semiconductor technology, new requirements have been put forward for the performance of various power electronic components, such as greater power and higher frequency. This requires that the soft magnetic materials used to process power inductors have lower high-frequency losses and better permeability frequency characteristics.
[0003] Traditional power inductors such as resonant inductors, PFC inductors, reactors, etc. mostly use metal powder cores as the core magnetic material. Due to their high high-frequency losses, they can no longer meet the working requirements of devices and equipment. In addition, the production of metal powder cores requires a large number of large presses with hundreds of tons, which has a high production cost.
[0004] Iron-based amorphous nanocrystals have both high magnetic induction and high magnetic permeability, which makes iron-based nanocrystalline ribbons have good application prospects in common-mode inductors.
[0005] Patent CN 114927303 A discloses a nanocrystalline magnetic core, which is made of an iron-based alloy amorphous straight strip, which is subjected to flash heating magnetoelastic stress treatment, wound into a ring-shaped magnetic core, and then subjected to magnetic field heat treatment. However, this nanocrystalline magnetic core is mainly suitable for the iron-silicon-boron-copper series alloy (Fe-Si-B-Cu series) system. The main purpose of its flash heating magnetoelastic stress treatment is to precipitate clusters, form α-Fe short-range order, reduce the area of FeB short-range order zone, effectively increase the number density of Cu clusters, and finally obtain high-density, small and uniform nanocrystalline grains. And it is necessary to further nanocrystallize and then apply magnetic field heat treatment to induce uniaxial anisotropy to compete with the average random anisotropy, change its magnetization behavior, and effectively improve its high-frequency characteristics and the ability of nanocrystalline inductors to suppress electromagnetic interference. It has the problems of narrow applicable system range and complicated processing steps, and the obtained inductor core is calculated to have a magnetic permeability of 20,000 or above at 100 kHz, which makes it difficult to cover products with a magnetic permeability below 20,000.
[0006] Patent CN 103117153 A discloses a method for preparing a common-mode inductor iron-based nanocrystalline core, including flat-plate flow liquid quenching method strip making, core winding and heat treatment steps. The core is wound with an iron-based nanocrystalline strip with a thickness of 18-24μm; the heat treatment is a crystallization heat treatment under a high-purity inert protective atmosphere or a composite magnetic field in a vacuum environment. This patented technology adopts an improved composite magnetic field heat treatment process, and the obtained common-mode inductor core has good frequency impedance characteristics and excellent anti-bias DC superposition capability, and improves the ability to attenuate common-mode signals. However, the heat treatment process has high requirements for control conditions, and the application field is limited to the field of common-mode interference suppression, which cannot meet the needs of differential mode or power inductors.
[0007] Patent CN 114694944 A discloses a method for preparing a nanocrystalline magnetic core, comprising: step S1: rolling a nanocrystalline ribbon to generate pre-treated nanocrystals; step S2: winding the pre-treated nanocrystals to generate a magnetic ring; step S3: heat treating the magnetic ring using a heat treatment method to generate the nanocrystalline magnetic core. This patent achieves lower coercivity and loss of the nanocrystalline magnetic core as a whole by applying ultrasonic rolling treatment to the nanocrystalline material and applying a transverse magnetic field during the heat treatment process, so that the nanocrystalline magnetic core has lower loss while having good device performance. However, the prior art still has the problems of complex processing steps and a narrow magnetic permeability coverage range.
[0008] Therefore, it is of great significance to obtain nanocrystalline magnetic cores and inductor products with low loss, good permeability frequency characteristics and excellent DC-bias performance, simplify their production process, reduce the difficulty of process control, and thus achieve the purpose of reducing their production costs. Summary of the invention
[0009] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide a method for preparing an amorphous nanocrystalline ribbon magnetic core. The preparation method of the present invention is prepared by roll-to-roll annealing of an amorphous nanocrystalline ribbon in one step, without further heat treatment and magnetic field treatment. The amorphous nanocrystalline component system has a wide range of adaptability, and the preparation method is simple and easy to control; the magnetic permeability of the obtained product can cover the range of 50 to 30,000 and is continuously adjustable.
[0010] Another object of the present invention is to provide an amorphous nanocrystalline ribbon magnetic core prepared by the above method.
[0011] Another object of the present invention is to provide the application of the above-mentioned amorphous nanocrystalline ribbon core in differential mode inductor core, power inductor core, resonant inductor core, energy storage inductor core and PFC inductor core.
[0012] The purpose of the present invention is achieved through the following technical solutions:
[0013] A method for preparing an amorphous nanocrystalline ribbon magnetic core, the specific preparation steps are as follows:
[0014] The amorphous nanocrystalline strip is subjected to a roll-to-roll annealing treatment, during which a tensile stress is applied along the length direction of the strip. The strip is then wound or punched into a closed magnetic circuit, or laminated into a block to obtain an amorphous nanocrystalline strip magnetic core.
[0015] Furthermore, the amorphous nanocrystalline ribbon is an amorphous ribbon whose component system is FeSiB, FeSiBC, FeNiSiB, or a nanocrystalline ribbon whose component system is Fe(and / or Ni, Co)CuNbSiB, Fe(and / or Ni, Co)CuMoSiB, Fe(and / or Ni, Co)CuPCSiB.
[0016] Further preferably, the amorphous nanocrystalline ribbon is an amorphous ribbon with a component system of FeSiB, FeSiBC, or FeNiSiB, and the annealing temperature of the roll-to-roll annealing treatment is 350 to 500° C., and the annealing time is 1 to 720 s.
[0017] Further preferably, the amorphous nanocrystalline strip is a nanocrystalline strip having a composition system of Fe(and / or Ni, Co)CuNbSiB, Fe(and / or Ni, Co)CuMoSiB, Fe(and / or Ni, Co)CuPCSiB, and the annealing temperature of the roll-to-roll annealing treatment is 500-650°C, and the annealing time is 1-720s.
[0018] Furthermore, the thickness of the amorphous nanocrystalline ribbon is 10 to 30 μm.
[0019] Furthermore, during the annealing process, the tensile stress applied along the length direction of the strip is 5 to 300 MPa.
[0020] Furthermore, the closed magnetic circuit is annular, rectangular or racetrack-shaped.
[0021] Furthermore, the winding or punching into a closed magnetic circuit refers to laminating and compounding amorphous nanocrystalline strips after multiple layers of roll-to-roll annealing and then winding or punching into a closed magnetic circuit; or laminating and compounding amorphous nanocrystalline strips after single-layer roll-to-roll annealing and then punching into a closed magnetic circuit.
[0022] An amorphous nanocrystalline strip wound magnetic core, characterized in that it is prepared by the above method.
[0023] Further preferably, the initial magnetic permeability of the amorphous nanocrystalline ribbon wound magnetic core is 50-30000, the AC loss at a magnetic induction intensity of 200mT and a frequency of 100kHz is 100-800mW / cm3 .
[0024] The above-mentioned amorphous nanocrystalline strip wound magnetic core is used in differential mode inductor magnetic core, power inductor magnetic core, resonant inductor magnetic core, energy storage inductor magnetic core and PFC inductor magnetic core.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The preparation method of the present invention is to prepare the amorphous nanocrystalline strip by roll-to-roll annealing in one step, without further heat treatment and magnetic field treatment. The amorphous nanocrystalline component system has a wide range of adaptability, the preparation method is simple and easy to control, and the preparation cost is low.
[0027] (2) The magnetic permeability of the product obtained by the present invention can cover the range of 50 to 30,000, and the magnetic permeability can be continuously adjusted by adjusting the tensile stress applied during the roll-to-roll annealing process, and the performance is excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of a device for roll-to-roll annealing of nanocrystalline strips in an embodiment of the present invention.
[0029] Figure 2 It is a comparison chart of the magnetic loss performance of the nanocrystalline ribbon wound magnetic core obtained in Examples 2 and 3 and the traditional metal magnetic powder core (Fe-Si magnetic powder core, MPP magnetic powder core, High Flux magnetic powder core).
[0030] Figure 3 hysteresis loop diagram of the nanocrystalline ribbon wound magnetic core obtained in Examples 2 to 4 and Example 6. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0032] Example 1
[0033] A method for preparing an amorphous strip wound magnetic core of this embodiment includes the following preparation steps:
[0034] The nominal composition is Fe a Si b B c , where a=78(at.)%, b=9(at.)%, c=13(at.)%, and the amorphous strip with a thickness of 28μm and a width of 10mm was subjected to a roll-to-roll annealing treatment at 450°C. During the annealing process, a tensile stress of 100MPa was applied along the length direction of the strip. The annealing time was 20s, and then the strip was wound into a closed magnetic circuit to obtain an amorphous strip wound magnetic core.
[0035] The schematic diagram of the roll-to-roll annealing device in this embodiment is as follows Figure 1 As shown. In the figure, 1 is the discharge tray of the strip; 2 and 4 are strip clamping devices, and tensile stress measurement sensors are installed on 2 and 4; 3 is a heating furnace, which can provide a heating environment within 700°C in the central cavity; 5 is a receiving tray. Its working principle is that the strip is led out from the discharge tray, enters the furnace cavity of the heating furnace 3 through the clamping device 2, is led out by the clamping device 4 after annealing, and is wound by the receiving device 5. Among them, the clamping devices 2 and 4 can realize the application of tensile stress through the speed ratio, and the tensile stress sensor can be used to feedback and adjust the stress in real time. The magnetic permeability of the annealed material is finally obtained, which is customized by the size of the tension. The greater the tension introduced during the annealing process, the lower the magnetic permeability of the obtained material. The application of tensile stress can also be achieved by adding weights between the clamping devices entering and exiting the furnace through the principle of leverage.
[0036] According to tests, the initial magnetic permeability of the amorphous strip wound magnetic core obtained in this embodiment is 1000, and the saturation magnetic induction intensity is 1.55T.
[0037] Example 2
[0038] A method for preparing a nanocrystalline ribbon wound magnetic core of this embodiment includes the following preparation steps:
[0039] The nominal composition is Fe bal. Si a B b Cu c Nb d , wherein a=15.5(at.)%, b=7(at.)%, c=1(at.)%, d=3(at.)%, a nanocrystalline ribbon with a thickness of 22μm and a width of 10mm was subjected to a roll-to-roll annealing treatment at 590℃, the roll-to-roll annealing device was the same as that in Example 1, a tensile stress of 100MPa was applied along the length direction of the ribbon during the annealing treatment, the annealing time was 25s, and then the ribbon was wound into a closed magnetic circuit to obtain a nanocrystalline ribbon wound magnetic core.
[0040] According to tests, the initial magnetic permeability of the nanocrystalline ribbon wound magnetic core obtained in this embodiment is 1000, and the saturation magnetic induction intensity is 1.23T.
[0041] The magnetic loss comparison between the nanocrystalline ribbon wound magnetic core obtained in this embodiment and the traditional metal magnetic powder core (Fe-Si magnetic powder core, MPP magnetic powder core, High Flux magnetic powder core) is as follows: Figure 2 As shown. Figure 2 The results show that the amorphous nanocrystalline magnetic core obtained by the present invention has lower magnetic loss than the traditional metal magnetic powder core.
[0042] The hysteresis loop of the nanocrystalline ribbon wound magnetic core obtained in this embodiment is as follows: Figure 3 shown.
[0043] Example 3
[0044] A method for preparing a nanocrystalline ribbon wound magnetic core of this embodiment includes the following preparation steps:
[0045] The nominal composition is Fe bal. Si a B b Cu c Nb d , wherein a=15.5(at.)%, b=7(at.)%, c=1(at.)%, d=3(at.)%, and a nanocrystalline ribbon with a thickness of 22μm and a width of 10mm was subjected to a roll-to-roll annealing treatment at 600°C. The roll-to-roll annealing device was the same as that in Example 1. During the annealing process, a tensile stress of 220MPa was applied along the length direction of the ribbon. The annealing time was 25s, and then the ribbon was wound into a closed magnetic circuit to obtain a nanocrystalline ribbon wound magnetic core.
[0046] According to tests, the initial magnetic permeability of the nanocrystalline ribbon wound magnetic core obtained in this embodiment is 100, and the saturation magnetic induction intensity is 1.23T.
[0047] The magnetic loss comparison between the nanocrystalline ribbon wound magnetic core obtained in this embodiment and the traditional metal magnetic powder core (Fe-Si magnetic powder core, MPP magnetic powder core, High Flux magnetic powder core) is as follows: Figure 2 As shown. Figure 2 The results show that the amorphous nanocrystalline magnetic core obtained by the present invention has lower magnetic loss than the traditional metal magnetic powder core.
[0048] The hysteresis loop of the nanocrystalline ribbon wound magnetic core obtained in this embodiment is as follows: Figure 3 shown.
[0049] Example 4
[0050] A method for preparing a nanocrystalline ribbon wound magnetic core of this embodiment includes the following preparation steps:
[0051] The nominal composition is Fe bal. Si a B b Cu c Nb d , wherein a=15.5(at.)%, b=7(at.)%, c=1(at.)%, d=3(at.)%, and a nanocrystalline ribbon with a thickness of 22μm and a width of 10mm was subjected to a roll-to-roll annealing treatment at 590°C. The roll-to-roll annealing device was the same as that in Example 1. During the annealing process, a tensile stress of 25MPa was applied along the length direction of the ribbon. The annealing time was 25s, and then the ribbon was wound into a closed magnetic circuit to obtain a nanocrystalline ribbon wound magnetic core.
[0052] According to tests, the initial magnetic permeability of the nanocrystalline ribbon wound magnetic core obtained in this embodiment is 10000, and the saturation magnetic induction intensity is 1.23T.
[0053] The hysteresis loop of the nanocrystalline ribbon wound magnetic core obtained in this embodiment is as follows: Figure 3 shown.
[0054] Example 5
[0055] A method for preparing a nanocrystalline ribbon wound magnetic core of this embodiment includes the following preparation steps:
[0056] The nominal composition is Fe bal. Si a B b Cu c Mo d , wherein a=9(at.)%, b=11(at.)%, c=0.5(at.)%, d=0.5(at.)%, a nanocrystalline ribbon with a thickness of 22μm and a width of 10mm was subjected to a roll-to-roll annealing treatment at 580℃, the roll-to-roll annealing device was the same as that in Example 1, a tensile stress of 50MPa was applied along the length direction of the ribbon during the annealing treatment, the annealing time was 30s, and then the ribbon was wound into a closed magnetic circuit to obtain a nanocrystalline ribbon wound magnetic core.
[0057] According to the test, the initial magnetic permeability of the nanocrystalline ribbon wound magnetic core obtained in this embodiment is 1000, and the saturation magnetic induction intensity is 1.69T.
[0058] Example 6
[0059] A method for preparing a nanocrystalline ribbon wound magnetic core of this embodiment includes the following preparation steps:
[0060] The nominal composition is Fe bal. Si a B b P c Cu d C e , wherein a=15.5(at.)%, b=7(at.)%, c=1(at.)%, d=3(at.)%, and a nanocrystalline ribbon with a thickness of 21μm and a width of 10mm was subjected to a roll-to-roll annealing treatment at 600°C. The roll-to-roll annealing device was the same as that in Example 1. During the annealing process, a tensile stress of 220MPa was applied along the length direction of the ribbon. The annealing time was 25s, and then the ribbon was wound into a closed magnetic circuit to obtain a nanocrystalline ribbon wound magnetic core.
[0061] According to tests, the initial magnetic permeability of the nanocrystalline ribbon wound magnetic core obtained in this embodiment is 100, and the saturation magnetic induction intensity is 1.93T.
[0062] The hysteresis loop of the nanocrystalline ribbon wound magnetic core obtained in this embodiment is as follows: Figure 3 shown.
[0063] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing an amorphous nanocrystalline ribbon magnetic core, characterized in that: The specific preparation steps are as follows: The amorphous nanocrystalline ribbon is subjected to a roll-to-roll annealing process, tensile stress is applied along the length direction of the ribbon during the annealing process, and then the amorphous nanocrystalline ribbon is wound or punched into a closed magnetic circuit, or laminated into a block to obtain an amorphous nanocrystalline ribbon magnetic core; The amorphous nanocrystalline ribbon is an amorphous ribbon with a component system of FeSiB, FeSiBC, and FeNiSiB, and the annealing temperature of the roll-to-roll annealing treatment is 350-500° C., and the annealing time is 1-720 s; Or the amorphous nanocrystalline ribbon is a nanocrystalline ribbon with a composition system of MCuNbSiB, MCuMoSiB, MCuPCSiB, wherein M represents Fe, Ni and / or Co; the annealing temperature of the roll-to-roll annealing treatment is 500-650° C., and the annealing time is 1-720 s; The initial permeability of the obtained amorphous nanocrystalline ribbon core is 50~30000, and the AC loss at a magnetic induction intensity of 200mT and a frequency of 100kHz is 100~800mW / cm 3 .
2. The method for preparing an amorphous nanocrystalline ribbon magnetic core according to claim 1, characterized in that: The thickness of the amorphous nanocrystalline ribbon is 10-30 μm.
3. The method for preparing an amorphous nanocrystalline ribbon magnetic core according to claim 1, characterized in that: The tensile stress applied along the length direction of the strip during the annealing process is 5-300 MPa.
4. The method for preparing an amorphous nanocrystalline ribbon magnetic core according to claim 1, characterized in that: The closed magnetic circuit is annular, rectangular or racetrack shaped.
5. The method for preparing an amorphous nanocrystalline ribbon magnetic core according to claim 4, characterized in that: The winding or punching into a closed magnetic circuit refers to laminating and compounding amorphous nanocrystalline strips after multiple layers of roll-to-roll annealing and then winding or punching into a closed magnetic circuit; or punching and cutting amorphous nanocrystalline strips after a single layer of roll-to-roll annealing into a closed magnetic circuit and then laminating and compounding multiple layers.
6. An amorphous nanocrystalline ribbon magnetic core, characterized in that: It is prepared by the method according to any one of claims 1 to 5.
7. Application of the amorphous nanocrystalline ribbon magnetic core according to claim 6 in a differential mode inductor magnetic core, a power inductor magnetic core, a resonant inductor magnetic core, an energy storage inductor magnetic core or a PFC inductor magnetic core.
Citation Information
Patent Citations
Common mode inductance iron-based nanocrystalline iron core and preparation method of the same
CN103117153A
Preparation method and preparation device of partially crystallized magnetically soft alloy strip and iron core
CN115206659A
Iron-based nanocrystalline magnetic core with low coercive force and low magnetic conductivity and preparation method
CN115995339A